Morocco : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that economic growth in Morocco has been volatile and insufficient to significantly reduce poverty and unemployment. Growth averaged 3 percent over the last decade. It has been volatile because of the dependency of agriculture on rainfalls. In 2004, macroeconomic and financial conditions remained stable. The unfavorable agricultural campaign is expected to affect macroeconomic conditions in 2005. The current account is likely to register a small deficit partly because of a high level of imports of food products and a higher oil bill.